The Kynurenine Pathway and Mediating Role of Stress in Addictive Disorders: A Focus on Alcohol Use Disorder and Internet Gaming Disorder - Jang, Joon Hwan; Yoo, So Young; Park, Yae Eun; Ji, Mi-Jung; Park, Hyun-Mee; Back, Ji Hyun; Lee, Ji Yoon; Kim, Dai Jin; Lee, Ji Eun; Choi, Jung-Seok (Frontiers in Pharmacology, 2022)
Stress plays an important role in the pathophysiology of addictive disorders. The kynurenine (KYN) pathway involved in neuroimmune and cognitive functions is activated under stress. However, the neuroimmunological–neurocognitive mechanisms in the role of stress in addictive disorders are unclear still now. Ninety-nine young adults aged 18–35 years (alcohol use disorder [AUD], N = 30; Internet gaming disorder [IGD], N = 34; healthy controls [HCs], N = 35) participated in this study. Stress levels, resilience, addiction severity, and neurocognitive functions were evaluated, and serum levels of tryptophan (TRP), 5-hydroxytryptamine (5-HT), KYN, and kynurenine acid (KYNA) were determined using liquid chromatography coupled with tandem mass spectrometry through blood samples. Both addictive disorder groups showed higher levels of stress, lower resilience, and impaired executive functions compared to the HC group. Importantly, the AUD group revealed significantly increased KYN levels and KYN/TRP ratios, as well as decreased KYNA levels and KYNA/KYN ratios compared to HCs (p < 0.001, p < 0.001, p = 0.033, and p < 0.001, respectively). The IGD group showed KYN levels and KYNA/KYN ratios intermediate between those of the AUD group and HCs. Furthermore, in the AUD group, the mediating effect of AUD on KYN through stress level was moderated by resilience (index of moderated mediation = -0.557, boot S.E = 0.331, BCa CI [-1.349, -0.081]). Stress may induce an imbalance in downstream of KYN pathway metabolites, and the KYN/TRP ratio may play as a neuromediator between stress and behavioral changes in both addictive disorders. This study suggests that regulation of the KYN pathway is critical in the pathophysiology of addictive disorders and it may serve as an important target for future treatment modalities.